Application of a PEM Fuel Cell Engine as a Small-Scale Power Generator for Small Cars with Different Fuel Concentrations: Fuel cell engine - Yusuf Dewantoro Herlambang; Wahyu Sulistiyo; Margana Margana; Nanang Apriandi; Marliyati Marliyati; Muji Setiyo; Jin Cherng Shyu (Universitas Muhammadiyah Magelang, 2023)
A fuel cell power generation system is a renewable energy system that works based on electrochemical processes and produces a direct electric current (DC). Specifically, a Proton Exchange Membrane (PEM) Fuel Cell can operate at low temperatures and produce an efficiency of around 40-60%. In this study, the performance test of the PEM Fuel Cell for power generation was carried out by supplying hydrogen gas using hydrogen from the electrolysis of the hydrogen generator with a variation of KOH catalyst solution with a concentration of 0.5 M; 1.0 M; 1.5 M; 2 M and using Ultra High Purity (UHP) hydrogen with various flow rates of 250 mL/min, 300 mL/min, 350 mL/min, 400 mL/min, 450 mL/min, and 500 mL/min. The test results showed that the output power of hydrogen produced by the electrolysis process was 10.8 W at a concentration of 1 M solutions at an input current of 20 A. The greater the concentration of the catalyst solution, the smaller the electrical power required for the electrolysis process. However, the hydrogen power supply produced by the hydrogen generator was not optimal, so it did not meet the needs of the PEM Fuel Cell. As a result, the PEM Fuel Cell could not work. Meanwhile, testing with UHP hydrogen produced the highest electrical power of 31.588 W at a flow rate of 450 mL/min with a load of 20 W. It indicates that the PEM Fuel Cell is optimal at the output power value with an efficiency of 69.80%.